2016
DOI: 10.1159/000453369
|View full text |Cite
|
Sign up to set email alerts
|

The HDM2 (MDM2) Inhibitor NVP-CGM097 Inhibits Tumor Cell Proliferation and Shows Additive Effects with 5-Fluorouracil on the p53-p21-Rb-E2F1 Cascade in the p53<sup>wild type</sup> Neuroendocrine Tumor Cell Line GOT1

Abstract: Background/Aims: The tumor suppressor p53 is depleted in many tumor cells by the E3 ubiquitin ligase mouse double minute 2 homolog (MDM2) through MDM2/p53 interaction. A novel target for inhibiting p53 degradation and for causing reexpression of p53wild type is inhibition of MDM2. The small molecule NVP-CGM097 is a novel MDM2 inhibitor. We investigated MDM2 inhibition as a target in neuroendocrine tumor cells in vitro. Methods: Human neuroendocrine tumor cell lines from the pancreas (BON1), lung (NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…A combinatory effect has been described to be effective in several other cancer entities [26-28, 39, 40]. Furthermore, Reuther et al [41] have recently demonstrated analogous effects concerning antiproliferative and chemosensitizing effects of another MDM2 antagonist, NVP-CGM097, on the p53 wild-type GOT-1 cell line, to which unfortunately only a limited number of research groups have access.…”
Section: Discussionmentioning
confidence: 99%
“…A combinatory effect has been described to be effective in several other cancer entities [26-28, 39, 40]. Furthermore, Reuther et al [41] have recently demonstrated analogous effects concerning antiproliferative and chemosensitizing effects of another MDM2 antagonist, NVP-CGM097, on the p53 wild-type GOT-1 cell line, to which unfortunately only a limited number of research groups have access.…”
Section: Discussionmentioning
confidence: 99%
“…For the combination experiments with BYL719/everolimus co-treatment, cell viability was assessed by “Cell Titer 96 Aqueous One Solution” MTS cell viability assay (Promega, Madison, WI, USA) according to the manufacturer`s instructions as previously described in detail [ 43 ]. Cells were treated with various concentrations of 1 μM—20 μM BYL719, 1 nM -10 nM everolimus, or a combination of both drugs for the indicated incubation times.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, inhibition of p53 modulators as MDM2 and induction of re-expression of p53 wild-type in GEP-NETs might be a promising therapeutic strategy ( 207 ) and should be investigated. Unfortunately, the majority of available GEP-NET cell lines do not reflect the wild-type TP53 status ( 208 ) or have not been assessed so far, making it difficult to estimate possible targets in those cell lines and thus limiting the possibilities for a transferable in vitro drug assessment ( 209 ).…”
Section: Novel Targets and Future Strategies In Netsmentioning
confidence: 99%
“…In the human SI-NET cell line KRJ-I, the MDM2 inhibitor nutlin-3 caused upregulation of p21 and inhibition of cell proliferation ( 209 ). In the human SI-NET cell line GOT1, the MDM2 inhibitor NVP-CGM097 caused upregulation of p53 and p21 and inhibition of cell proliferation ( 208 ). Furthermore, NVP-CGM097 showed additive effects with 5-fluorouracil on cellular survival decrease because of enhanced downregulation of the p53-p21-Rb-E2F1 cascade in the p53 wild-type NET cell line GOT1 ( 208 ).…”
Section: Novel Targets and Future Strategies In Netsmentioning
confidence: 99%